Health Promotion Using Animated Videos to Increase Elementary Students' Knowledge and Readiness in Dealing with Menarche - Diana Hartaty Angraini; Erika Yulita Ichwan; Yulia Sari (Women, Midwives and Midwifery, 2021)
Background: Entering puberty, a young girl will experience various changes. One of them is having menstruation. Menstruation is one of the critical events in life that girls should know. It happens because menstruation does not come once and then disappears in a woman's life, but there is a menstrual cycle that comes every month. Young girls need adequate information to deal with menstruation for the first time. Knowledge should be given to the young girl to deal with menstruation, such as physical and psychic changes. This study aimed to determine the effect of health promotion through animated videos on increasing the knowledge and attitudes of elementary school children facing menarche Methods: This quantitative study used a quasi-experimental design. The population in this study was all 5th-grade elementary school students who had not had menstruation. The sample size was 38 respondents for each group, intervention, and control Result: The results showed a difference in knowledge scores between the intervention and control groups with a p-value of 0.000. There was a difference in attitude scores in the control and intervention groups with a p-value of 0.031. Conclusion: There is an increase in knowledge scores and attitudes before and after the intervention. The difference in the intervention group's knowledge and attitude level scores and the control group and the animated video preparation of menarche influence knowledge and attitude.